Motivating deprescribing conversations for patients with Alzheimer's disease and related dementias: a descriptive study - Mary T. Antonelli; John S. Cox; Cassandra Saphirak; Jerry H. Gurwitz; Sonal Singh; Kathleen M. Mazor (SAGE Publishing, 2022)
Introduction: Older adults with Alzheimer's disease and related dementias (ADRD) are at increased risk of harm due to prescribing of potentially inappropriate medications. Encouraging patients and caregivers to talk with their providers about potentially inappropriate medications could stimulate deprescribing. Our objective was to explore whether mailing educational materials to patients with ADRD might activate patients or caregivers to initiate a conversation with their provider about potentially inappropriate medications. Methods: We conducted semi-structured interviews with patients with ADRD, caregivers of patients with ADRD, and healthcare providers. All participants were shown educational materials referencing potentially inappropriate medications and suggestions to promote deprescribing. Interviews explored reactions to the materials, the idea of patients and caregivers initiating a conversation about deprescribing, and the deprescribing process. Interview transcripts were analyzed using inductive thematic analysis. Results: We conducted a total of 27 interviews: 9 with caregivers only, 2 with patients only, 3 with patient-caregiver dyads, and 13 with providers. Patients and caregivers reported that if a medication might cause harm, it would motivate them to talk to their provider about the medication. Trust in the provider could facilitate or inhibit such conversations; conversations would be more likely if there were prior positive experiences asking questions of the provider. Providers were receptive to patients and caregivers initiating conversations about their medications, as they valued deprescribing as part of their clinical practice and welcome informed patients and caregivers as participants in decision-making about medication. Conclusion: Mailing educational materials about potentially inappropriate medications to community-dwelling patients with ADRD may promote deprescribing conversations. Ongoing pragmatic trials will determine whether such interventions stimulate deprescribing conversations and achieve reductions in prescribing of inappropriate medications. Plain Language Summary Encouraging patients with Alzheimer's disease to talk with their providers about medications that may cause harm Introduction: Older adults with Alzheimer's disease and related dementias (ADRD) are sometimes prescribed medications that may cause harm, especially when taken for extended periods of time. Patients and their caregivers may not know about the risks. Doctors know of the risks but may not address them due to competing priorities or other challenges in providing care to these patients with complex needs. Encouraging the patient or their caregiver to talk to their doctor about their medications might help to reduce the use of medications that are not beneficial. This study's goal was to explore whether sending educational materials to patients with ADRD might encourage patients or caregivers to ask their doctor about their medications. Methods: We interviewed patients with ADRD, caregivers, and doctors. We showed them educational materials that suggested patients and their caregivers talk to their doctor about reducing or stopping medications that may be harmful. We asked for reactions to the materials and to the idea of talking to the doctor about stopping the medication. Results: We conducted 27 interviews: 9 with caregivers only, 2 with patients only, 3 with patient-caregiver dyads, and 12 with doctors. Patients and caregivers said learning that a medication might cause harm would motivate them to talk to their doctor about the medication. Trust in their doctor was important. Some patients and caregivers were comfortable asking questions about medications, while others were reluctant to challenge the doctor. Doctors were open to patients and caregivers asking about medications and felt it was important that patients not take medications that are not needed. Conclusion: Sending educational materials to patients with ADRD and caregivers may encourage them to talk with their doctors about stopping or reducing medications. Studies are needed to learn whether such materials lead to reductions in prescribing of potential harmful medications.